Founding entrepreneur's dilemma: Stay or exit the firm following an acquisition? An international comparison. Issue 1 (February 2022) - Sanguineti, Francesca; Majocchi, Antonio; Cavusgil, S. Tamer
Highlights: Founding entrepreneurs' experiences and characteristics influence their choice to remain or exit their company after it has been acquired. Founders with prior entrepreneurial and international experience and higher education levels display a greater propensity to exit. After the acquisition, founding entrepreneurs with longer tenure tend to remain in the firm. Compared to their North American counterparts, entrepreneurs residing in Europe and Asia show a higher propensity for remaining in their firms. Abstract: Many differences exist between founders that decide to maintain ownership of their firm and those that surrender ownership. Few studies have addressed what founders decide to do once their firm has been acquired, and even fewer have looked at this phenomenon from an international point of view. By utilizing Prospect Theory, we address this research question through a database of 6, 271 founding entrepreneurs from North America, Europe, and Asia. We compare and contrast founders who choose to remain within the company with those that exit and move on to a different activity after their enterprise has been acquired. Our empirical analysis suggests that founders' tenure, entrepreneurial experience, education level, international experience, and their world region of residence, together with the firm's stock exchange listing, act as significant antecedents of the founding entrepreneur's choice to exit the firm after acquisition.